2014
DOI: 10.1111/jphp.12217
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid design to optimize preparation of lopinavir loaded solid lipid nanoparticles and comparative pharmacokinetic evaluation with marketed lopinavir/ritonavir coformulation

Abstract: SLNs enhanced oral bioavailability and improved distribution profile of LPV to HIV reservoirs and hence could be better alternative to LPV/RTV coformulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…In separate rats dosed intraduodenally with a solid lipid NP formulation of lopinavir, cumulative lopinavir concentrations in lymph fluid were 9.68 μg for the nanoformulation compared to 1.97 μg for the conventional formulation 6 hours after administration [106]. Negi et al reported similar observations using another solid lipid NP of lopinavir that was fabricated using a hot self nano-emulsification technique [107, 108]. Although the gut lymphatic-targeting mechanism of lipid-formulated drugs is not clear, it is believed to be similar to dietary fat absorption.…”
Section: Introductionmentioning
confidence: 91%
“…In separate rats dosed intraduodenally with a solid lipid NP formulation of lopinavir, cumulative lopinavir concentrations in lymph fluid were 9.68 μg for the nanoformulation compared to 1.97 μg for the conventional formulation 6 hours after administration [106]. Negi et al reported similar observations using another solid lipid NP of lopinavir that was fabricated using a hot self nano-emulsification technique [107, 108]. Although the gut lymphatic-targeting mechanism of lipid-formulated drugs is not clear, it is believed to be similar to dietary fat absorption.…”
Section: Introductionmentioning
confidence: 91%
“…As lipid concentration was increased, the entrapment efficiency was found to be increased from 18 to 95%. This was expected because at higher lipid concentration, viscosity of lipid phase will be increased which will result into faster solidification which in turn will prevent drug diffusion from inner phase to aqueous phase [20].…”
Section: Influence Of Lipid Concentrationmentioning
confidence: 99%
“…Lopinavir‐loaded SLNs were prepared by previously reported warm oil‐in‐water (O/W) micro‐emulsion technique . Briefly, oil phase was prepared by dissolving LPV (10 mg) in molten mass of SA (100 mg) maintained at 75 °C.…”
Section: Methodsmentioning
confidence: 99%
“…To improve therapeutic effectiveness of anti‐retroviral drugs, lipid‐based nanocarrier systems like solid lipid nanoparticles (SLNs) have been extensively studied over the last decade . It is widely reported that SLNs significantly enhances the plasma exposure of poorly bioavailable compounds by increasing drug permeability or absorption and reducing drug clearance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation